The Future of our Foreign Trade: Summary - Vanderlip, Frank A.; Williams, John H. (The Review of Economics and Statistics, 1920)
THE purpose of the present article is to throw some further light upon the future of our foreign trade by an analysis of our balance of merchandise trade in I9I9 and of the items which served as an offset against our huge surplus of exports. The total figures for the year show a continuance of the abnormal conditions of the war period a large surplus of exports financed mainly by the extension of credit by our government to foreign governments. But there are indications that a return to normal conditions of trade is already under way. The movement began with the unpegging of the exchanges in the spring of I9g9 and the lifting of our embargo on gold. Despite some subsequent rather alarming occurrences, notably the spectacular fall of the exchanges in the late fall and early winter just passed, we have had more recently some further evidence pointing in the same direction especially the recent importations of gold from Great Britain, and the announcement by the Treasury last January of its definitive abandonment of the policy of government credit extensions to the Allies to finance exports. What will be the state of our trade balance when trade is once again upon a normal basis; and what is more important, how soon, and by what stages, will that normal condition be reached ? On these questions the analysis of our balance of international payments provides the clearest evidence yet available. The article begins with an analysis of the visible trade balance merchandise and specie; then presents the available data (collected with the assistance of J. P. Morgan and Co., the Guaranty Trust Company of New York, the United States Treasury, the Shipping Board, and others) upon the invisible items which served to offset the large surplus of merchandise and specie; and concludes the first section with a summary statement of our balance of international payments as a whole. This is followed by a second section setting forth certain conclusions concerning the future of our foreign trade. The analysis of the merchandise trade shows the principal changes which occurred in I919 in (i) commodities exported and imported, (2) our trade balances with the various continents and individual countries, and (3) the trend of exports and imports through the year. The outstanding facts were: (i) The enormous value figures of the war period were exceeded, exports, imports, and excess of exports over imports all reaching figures far in excess of anything ever before witnessed. The increase was due mainly to further price inflation, but compared with I9I8 there was an important gain in the quantity figures also. The principal gains in exports were in raw materials and food products; manufactures, owing to the virtual cessation of military exports, increased only slightly. Sixty-nine per cent of the total gain in exports over I9I8 ($I,759,000,000) was in five commodities, raw cotton, tobacco leaf, hog products, wheat and wheat flour, and leather goods. In imports also the chief increases were in raw materials and food products. Ninety-three per cent of the total increase in imports ($873,000,000) was in six commodities, hides and skins, crude rubber, coffee, cane sugar, raw silk, and precious stones. (2) Our trade balances by continents and countries were in general similar to those of the war period, but there were some striking differences in detail. The chief change was in our trade balance with Europe, which increased from a favorable balance of $3,541,000,000 in I918 to a favorable balance of $4,43s,000,ooo in I9I9. This increase, however, was not due to increased buying from us by the Allies, but to the very large increase in our exports to the European neutrals (from $171,000,000 in I918 to $866,ooo,ooo in I919), which caused our favorable balance with those countries to increase from $ii8,000,000 in I9I8 to $686,ooo,ooo in I919. This expansion of our exports to neutral Europe was one of the most outstanding features of the year. With North America our balance continued favorable but diminished considerably. With South America and Asia our balance continued against us, but was somewhat reduced in amount. (3) The most striking and significant feature of our foreign trade in I9g9 was the marked change in the trend of trade during the year. The quarterly and half-yearly figures show that the record balance for the year was due entirely to the expansion of exports in the first half of the year. This expansion was merely the continuation of that growth of exports which began in the first year of the war. The peak was reached in June, I9I9. Then came the beginning of the new swing in our foreign trade. Exports in the second half of the year declined despite the continued rise of prices and the inclusion of the harvest exports. Imports showed a continuance of the strong upward movement which had set in at the beginning of the year. This steady increase in imports was the outstanding fact of the year. The trade balance for the second half of the year showed in consequence of it a decline of $927,000,000 (from a favorable balance of $2,547,000,000 in the first half of the year to one of $I,620,ooo,ooo in the second half-year). The gold movement in I919 exhibited an apparently anomalous, but really quite logical, situation. In the year of our largest favorable trade balance we had our heaviest loss of gold, net gold exports (considering the $I3I,000,000 gold held by the Bank of England for the federal reserve banks as a virtual import) amounting to $i6o,ooo,ooo. This was due to the removal of our gold embargo and the consequent outflow to settle our adverse balances in Latin America and the Orient; while, the European gold embargoes being still in force, the receipt of gold by us on balance due from Europe was artifically restricted. The net result was that whereas in the war period the inflow of gold (which occurred almost entirely in the early years, and amounted to $I,029,000,000 net) constituted a partial offset to the trade balance, in i919 the net gold movement represented an addition to the trade balance, increasing it to $4,328,ooo,ooo. To this huge surplus of exports of merchandise and species are added our net receipts of interest on capital invested abroad ($I22,000,000) and also our net receipts from ocean freights earned by American shipping and from the sale of ships ($93,ooo,ooo); so that our true surplus of credit items was $4,543,-